Theoretical Study on the $K_{α}$ Transition Properties of F-Like Ions (Journal of Atomic and Molecular Sciences, 2010)
In a recent calculation on $K_{α}$ transition properties of fluorine-like ions (10 $≤$ Z $≤$ 79) by Sur et al. [Phys. Rev. A 77 (2008) 052502], it was found that there is a crossover between $K_{α1}$ and $K_{α2}$ transition probabilities with increasing of atomic number Z. In order to examine this unusual behavior, a further theoretical study has been carried out by using multi-configuration Dirac-Fock (MCDF) method. In the calculation, Breit interaction, electron correlation and quantum electrodynamics (QED) effects have been included. The present study shows a contrary conclusion to the earlier theoretical results.